Theodor von Lerch as a Skier before Dispatching to Japan - ARAI, Hiroshi (Journal of Ski Science, 2004)
The purpose of this paper is the role of Theodor von Lerch as a skier before his dispatch to Japan. The historical materials used here are the official documents archived at the General Staff Office in Wien and the articles left by Lerch. The results of this study can be summarized as follows: 1) The start of Lerch's skiing in his own country was in relation to his duty in the army. 2) Lerch had worked hard in an alpine ski club, so he had many experiences to promote activities, such as skitours, ski-lessons and ski-races. 3) Lerch made efforts to introduce skiing to the army from his position as a General Staff Officer in the Ministry of National Defence. 4) Lerch had cooperated with Zdarsky for some time in order to compile a manual of the army on skiing techniques. so he mastered the various techniques suitable for military use very well. 5) Lerch as a skier before dispatching to Japan had learned many techniques in skiing and took the responsibility to import skiing into the army, as well as spread skiing to the populace.